Improving Teacher Performance Through Principal Leadership (Case Study at SMP Al Falah, Bandung City) - Fuad Rinaldi; Endang Komara; Agus Mulyanto; Miftahussalam Miftahussalam; M Firman S; M Matin S (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the importance of improving teacher performance in terms of the leadership of the school principal. This study aims to describe the increase in teacher performance through the leadership of the principal at SMP Al Falah Dago Bandung. This study uses a qualitative research method with a case study approach and is descriptive in nature. The place and time of this research is SMP Al Falah Dago Bandung in Odd Semester 2023/2024. Data collection techniques namely observation, interviews and documentation. Informants/sources of information in this study were the Principal of SMP Al Falah, Deputy Principal of SMP Al Falah and SMP Al Falah teachers. Data analysis techniques carried out were data reduction, data presentation, and verification. The results of this study explain 1) SMP Al Falah is located in Dago Bandung, Jalan Cisitu 52 Bandung City under the auspices of the Insan Al Falah Foundation Dago Bandung, 2) Teacher performance is the ability to carry out the work of a teacher in carrying out his duties and responsibilities at the school where he teaches both in the form of knowledge and skills, 3) Principal leadership is the ability to lead all existing resources in a school to achieve common goals, and 4) Al Falah Dago Bandung principal leadership is a paternalistic and charismatic leadership style with this style influencing teacher performance. The conclusion of this study is that teacher performance can be improved through the leadership of the school principal.